2016
DOI: 10.3389/fmicb.2016.00790
|View full text |Cite
|
Sign up to set email alerts
|

Listeria ivanovii Infection in Mice: Restricted to the Liver and Lung with Limited Replication in the Spleen

Abstract: Listeria monocytogenes (LM) vectors have shown much promise in delivery of viral and tumor antigens for the development of vaccines. L. ivanovii (LI) is a closely related bacterium with a similar intracellular life cycle that may offer advantages over LM because it is not a human pathogen, but can infect other animal species. Recent studies show that recombinant LI expressing Mycobacterium tuberculosis antigens is effective in inducing protective immunity in mouse models, demonstrating the potential of LI as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…It is not surprising that both strains failed to induce antigen-specific cellular immunity in the spleen because they did not establish a durable infection in the spleen. As we reported previously, when LI invaded the lung via the respiratory tract, the typical infection lesions that resulted seemed isolated and densely packed 18 . This phenomenon can be attributed to the unique feature of ivanolysin O (ILO).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…It is not surprising that both strains failed to induce antigen-specific cellular immunity in the spleen because they did not establish a durable infection in the spleen. As we reported previously, when LI invaded the lung via the respiratory tract, the typical infection lesions that resulted seemed isolated and densely packed 18 . This phenomenon can be attributed to the unique feature of ivanolysin O (ILO).…”
Section: Discussionsupporting
confidence: 75%
“…After intravenous administration, bacteria were delivered via circulation of the blood and directly entered peripheral immune organs such as the spleen and liver, where they were phagocytosed by phagocytes and dendritic cells, thus inducing efficient systemic immune responses 17 . Our earlier studies showed that wild-type LI mainly localized in the lung after intranasal administration 18 . Therefore, LIΔ-Rv3875 and LIΔ-Rv0129c elicited lung-localized antigen-specific T cell immune responses www.nature.com/scientificreports www.nature.com/scientificreports/ and pulmonary mucosal SIgA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In recent years, some countries have regular monitoring of L. monocytogenes and the research orientation also extend to more fields with some outbreaks of foodborne infections by L. monocytogenes being reported (Gillesberg Lassen et al 2016). L. ivanovii is associated with abortion in ruminants, especially sheep, and has the ability to cause severe clinical symptoms, such as bacteremia, mesenteric adenitis, uterine discharge, and stillbirth, but does not cause encephalitis (González-Zorn et al 1999, Ramage et al 1999, Guillet et al 2010, Beye et al 2016, Zhou et al 2016. L. ivanovii has also been reported to cause human listeriosis (Guillet et al 2010, Beye et al 2016.…”
Section: Introductionmentioning
confidence: 99%